Criminal Asset Forfeiture In The Sense Of Extraordinary Confiscation - Hadi Supriyanto; Safrin Salam; Waode Novita Ayu Muthmainna; Hasni Hasni; Supardi Supardi (Musamus Law Review, 2023)
The meaning of confiscation in principle explains that the proceeds of crime must be confiscated, this aims to prevent the convict from being able to utilize or benefit from the criminal acts he committed. Conceptually, confiscation is a State action that is carried out carefully and procedurally. This means that forfeiture requires a strict legal evidentiary instrument first because without it there could be abused of power in its implementation. In Indonesia, the meaning of confiscation is the efforts of law enforcement officials in their interests to prove cases and / or investigations (Article 1 point 16 of the Criminal Procedure Code), with this understanding, the intended confiscation is limitative. The procedure for confiscation is regulated in articles 128, 129 and 130 of the Criminal Procedure Code or the same points as ordinary confiscation. The goal of criminalizing behaviour that generates huge profits illegally is not enough just to punish physically, even if caught and punished, it is possible that these criminals can enjoy their illegal profits. For this reason, a set of administrative rules is needed that can be used as a foothold for deprivation in the face of criminalization.